Desain UI/UX Aplikasi Edukasi FIDEXA-SD Menggunakan Design Thinking dan Figma - Yaasiin, Muhammad; Hanif, Isa Faqihuddin (LPPM Universitas Mulia, 2025)
This study explores the UI (User Interface) and UX (User Experience) design process of an educational application called FIDEXA-SD, developed specifically for elementary school students and teachers. The core problem identified is the limited availability of digital learning tools that are both engaging for young learners and practical for educators. To address this, the Design Thinking approach was implemented through five iterative stages: Empathize, Define, Ideate, Prototype, and Test. Using Figma, the research team designed interactive prototypes for student and teacher interfaces. Data were gathered through interviews, questionnaires, and usability testing involving 5 students from grades 2 to 4 and 3 teachers. Results showed that students found the visual design attractive and intuitive, while teachers appreciated the clean and functional dashboard layout. Some usability issues, such as confusing quiz navigation and unclear material upload options, were uncovered and addressed through design iteration. This study highlights how combining Design Thinking with Figma can effectively produce user-centered designs tailored to the needs of both learners and educators. The findings also provide a solid foundation for future development and real-world classroom implementation.